2018
DOI: 10.1253/circj.cj-17-1172
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With High CHA<sub>2</sub>DS<sub>2</sub>-VASc Scores Need High Intensity of Anticoagulants After Valve Surgery?

Abstract: Background: Asian patients on warfarin therapy usually have lower international normalized ratio (INR) intensities than those recommended by Western clinical practice guidelines. This study evaluated whether a high INR reduces the incidence of thromboembolism (TE) or bleeding events in Asian patients with high CHA2DS2-VASc scores after valve surgery. Methods and Results:Data of adult patients after valve surgery were retrieved from an integrated healthcare information system of a single hospital between 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…There are studies involving patients applying to EDs due to warfarin-related complications, and the ratio of patients within the therapeutic range is generally consistent with our findings. [14][15][16] Although an increase in INR level from 1 to 2 indicates a twofold hemorrhage risk, it has been reported that the incidence of intracranial hemorrhage is higher after values greater than 3.9. 4,17 The supratherapeutic INR rate in our study was 34.4% and the number of participants who reported major hemorrhage in the past was higher compared to the general literature (13.9%).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies involving patients applying to EDs due to warfarin-related complications, and the ratio of patients within the therapeutic range is generally consistent with our findings. [14][15][16] Although an increase in INR level from 1 to 2 indicates a twofold hemorrhage risk, it has been reported that the incidence of intracranial hemorrhage is higher after values greater than 3.9. 4,17 The supratherapeutic INR rate in our study was 34.4% and the number of participants who reported major hemorrhage in the past was higher compared to the general literature (13.9%).…”
Section: Discussionmentioning
confidence: 99%
“…However, this target INR is not popularly accepted even in Japan [23]. Recently, two studies have suggested that a lower target INR (1.5 to 2.6) may be appropriate for East Asians with mechanical valves than that recommended by Western guidelines [23,24]. Figure 1 shows the enrollment, allocation, and follow-up of the trial.…”
Section: Patientsmentioning
confidence: 99%
“…The selection of prosthetic valve was made with a joint discussion between the surgeons and the patients according to the current valve surgery guideline, clinical condition, anticoagulant compliance and the patients’ subjective willing. The target international normalized ratio (INR) for patients with mechanical prostheses replacement was controlled between 2.0 and 2.5 for mitral position and between 1.5 and 2.5 for aortic position, controlled directly by the surgeon and the rheumatologist [ 5 ]. For patients receiving xenograft prostheses, Vitamin-K antagonist was prescribed for 3 months after the operation.…”
Section: Methodsmentioning
confidence: 99%